Combining virtual reality and 3D‐printed models to simulate patient‐specific dental operative procedures—A study exploring student perceptions. (17th September 2021) - Towers, Ashley; Dixon, Jonathan; Field, James; Martin, Rachel; Martin, Nicolas
Abstract: Introduction: Students face a number of challenges in translating the skills acquired in pre‐clinical simulation environments to the delivery of real patient care. These are particularly emphasised for complex operative procedures such as tooth preparations for indirect restorations. This paper reports student perceptions of a novel approach designed to improving student confidence when undertaking operative procedures on patients for the first time, by providing patient‐specific simulation using virtual reality (VR) and 3D‐printed models of the student's real clinical case. Materials and Methods: Students practised on patient‐specific models, in the presence of a clinical tutor, firstly using VR simulation then with 3D‐printed models in a clinical skills laboratory. The students then carried out the operative procedure on their patients, on the third occasion of practice. After providing the treatment for their patients, students attended a semi‐structured interview to discuss their experiences. The qualitative data were analysed using two forms of inductive analysis. Results: Students most frequently cited: the value of the educator, increased confidence and efficiency during the clinical procedure, improved patient confidence and the complementary benefits of the two simulation modalities. Thematic analysis of participants' responses uncovered five key themes: The value of virtual reality dental simulators The value of clinical skills laboratory simulation with 3D‐printed models The value of educator engagement The impact on the clinical procedure and the patient The VR and clinical skills laboratory balance Conclusion: This paper reports the early findings of an intervention that improves dental student confidence through the use of patient‐specific VR exercises and 3D‐printed models. These provided an incremental learning experience for an operative clinical procedure, prior to treatment of the live patient. Early results suggest this is a positive experience for the students, providing a valuable contribution to their confidence and preparedness.